PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), DAN TOTAL ASSETS TURNOVER (TATO) TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2020 - Yuslinda Nasution; Guston Sitorus (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2022)
This research was conducted to examine the effect of Current Ratio (CR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) on profit growth. The population in this study were all basic and chemical manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The sampling technique used was purposive sampling with a sample of 32 companies. The analytical method used in this research is descriptive analysis and multiple linear regression. The type of data in this study uses secondary data. The results of this study indicate that the effect of Current Ratio (CR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) on profit growth is 30%. Partially Current Ratio (CR) and Debt to Equity Ratio (DER) have no significant effect on profit growth, while Total Asset Turnover (TATO) has a significant effect on profit growth in basic and chemical manufacturing companies listed on the Indonesia Stock Exchange for the 2017 period. – 2020.